Simulasi Pengaruh Submerged Breakwater Terhadap Karakteristik Gelombang - Almanna, Fajri; Sutikno, Sigit; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Waves moved from sea to coast cause erosion on the shore. The purpose of this research is to simulate the effect of submerged breakwater on wave characteristics. The method used in this research was wave simulation with several variations of the wave period, the number of breakwater and the distance between two breakwaters. The simulation used was laboratory simulation and numerical method using CADMAS Surf 2D software. The results showed that the wave height decreased with the addition of breakwater and the addition of the distance between two breakwaters. Furthermore, the wave starts to change when Froude number (fr) = 2,8. Based on the simulation froude value is generated > 1 so it still less effective to preventing abrasion.Keywords : Submerged Breakwater, CADMAS Surf 2D, Characteristics of Wave